2014
DOI: 10.1371/journal.pone.0099221
|View full text |Cite
|
Sign up to set email alerts
|

Rumen Cellulosomics: Divergent Fiber-Degrading Strategies Revealed by Comparative Genome-Wide Analysis of Six Ruminococcal Strains

Abstract: BackgroundA complex community of microorganisms is responsible for efficient plant cell wall digestion by many herbivores, notably the ruminants. Understanding the different fibrolytic mechanisms utilized by these bacteria has been of great interest in agricultural and technological fields, reinforced more recently by current efforts to convert cellulosic biomass to biofuels.Methodology/Principal FindingsHere, we have used a bioinformatics-based approach to explore the cellulosome-related components of six gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 83 publications
5
74
0
3
Order By: Relevance
“…[53,54] A large effort in comparative genomics was able to identify highly-conserved, functionally-indispensable modules and residues. [55,56] Since the heterogeneity and flexibility of the full-length cellulases and cellulosomes are impediments to crystallization, small angle X-ray scattering (SAXS) measurements have helped to confirm the overall architecture of the cellulosome. [57] Recent advances in instrumentation and automation (in particular, the routine use of synchrotron radia-tion, exploitation of anomalous diffraction methods in protein crystallography, and adaptation of beam lines to perform SAXS on proteins in solution) provide more sophisticated experi-mental techniques to study these challenging and intricate cellulolytic assemblies.…”
Section: Bacterial Breakdown Of Crystalline Cellulosementioning
confidence: 99%
See 1 more Smart Citation
“…[53,54] A large effort in comparative genomics was able to identify highly-conserved, functionally-indispensable modules and residues. [55,56] Since the heterogeneity and flexibility of the full-length cellulases and cellulosomes are impediments to crystallization, small angle X-ray scattering (SAXS) measurements have helped to confirm the overall architecture of the cellulosome. [57] Recent advances in instrumentation and automation (in particular, the routine use of synchrotron radia-tion, exploitation of anomalous diffraction methods in protein crystallography, and adaptation of beam lines to perform SAXS on proteins in solution) provide more sophisticated experi-mental techniques to study these challenging and intricate cellulolytic assemblies.…”
Section: Bacterial Breakdown Of Crystalline Cellulosementioning
confidence: 99%
“…Mechanical forces can conceivably play a very important role in the cellulosome physiology; in the first instance the bacteria is a mesoscopic object ("microscopic" in biological jargon) and as such is not only subjected to Brownian motion, like molecules in solution, but will additionally feel longer-range hydrodynamic forces (e.g., in a turbulent cow stomach or capillary flow gradients in moist soil). [56] Under these conditions maximum holding strength and maximum catalytic efficiency seems to be needed. It is therefore not surprising that the mechanical strengths measured in cellulosome studies are among the highest found so far in biological systems.…”
Section: The Role Of Mechanostability In Nanoscale Functionmentioning
confidence: 99%
“…We, therefore, selected the rumen microbiome for its highly complex nature, together with its main functionality of plant cell wall deconstruction (Qi et al, 2010;Mizrahi, 2013;Dassa et al, 2014). This gap of knowledge stems from the fact that these complexes have been mainly studied in cultivated isolated microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Este grupo de microrganismos possui bactérias especializadas na degradação da parede celular vegetal, apresentando um sistema complexo multi-enzimático chamado celulossoma (DASSA et al, 2014). A bactéria anaeróbica…”
Section: Dias Diasunclassified